IMF Staff papers : Volume 17 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1970)
This paper analyzes the determination of monetary policy is an exercise that must include the organization of information so that proper conclusions may be reached regarding the application of policy instruments. The information on which policies have to be based is frequently a complex set of interrelated data. It is extremely difficult to obtain a reasonable view of the future unless it is possible to assign some quantitative magnitudes to the significant monetary aggregates. In all countries, but particularly in the less developed, the immediate monetary situation may be judged largely in terms of the level of international reserves and the comparative rates of growth in bank credit and money. Central bankers are faced with the terrifying complexity of information and relations between variables that typifies the financial structure of any economy. In order to classify the statements and to clarify the financial relations in an economy, the bankers need an organized arrangement of the available information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet